Generic skills in vocational education and training : research readings - Gibb, Jennifer [Herausgeber] (NCVER, 2004)
"Possessing generic or employability skills is vital in the current labour market. The vocational education and training (VET) sector, like other education sectors, must ensure its clients gain and develop generic skills. This volume of readings summarises NCVER managed research into generic skills undertaken in 2001 and 2002. The work covers four main topics: defining and specifying generic skills; exploring training providers', teachers' and learners' perspectives of these skills; exploring the workplace perspective of generic skills; and assessing these skills. To ensure people gain the generic skills they need, the research suggests improving the documentation of these skills in training packages, and sharing good teaching, learning and certifying practice." (Editor, BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; G 1.2.3.1 Potenziale; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; I 2.3.5 Australien, Ozeanien; Berufsbildungssystem; Beziehung Bildungssystem Beschäftigungssystem; Qualifikation; Beschäftigungsfähigkeit; Beschäftigungsentwicklung; Arbeitsumwelt; Australien